The dry [videorecording (DVD)] - Bana, Eric; O'Reilly, Genevieve, 1977-; O'Donnell, Keir; Polson, John, 1965- (IFC Films, 2022)
Aaron Falk goes back home to his drought-stricken town to attend a tragic funeral. However, his return reopens the door to the unsolved death of a teenage girl.